Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T19:43:05+01:00
A)
-8x-16+3x+15=-4x-6+8x-4
-16x+3x+4x=16-15-6-4
-9x=-9
x=1
b)
24-6x+10x-25=4x-4-12+3x
-3x=-15
x=5
c)9-3x+2x=8-2x+2
x=1
d)4x+5-3x-6=4+2x-4
-x=1
x=-1
e)4-15+5x=-x-3-2x
8x=8
x=1
f)x-7-2x=2x-2+1
-3x=6
x=-2
2010-03-18T20:04:09+01:00
-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x+-6+8x-4
-8x+3x+4x-8x=-6-4+16-15
-9x=-9 /:(-9)
x=1

6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x=15 /:(-3)
x=-5

3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=8+2-9
x=1

4x+5-(3x+6)=2(2+x)-4
4x+5+3x-6=4+2x-4
4x+3x-2x=4-4-5+6
5x=1 /:1
x=1/5


4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
5x-2x+x=-3+15-4
4x=8 / :4
x=2


x-(7+2x)=2(x-1)+1
x+7-2x=2x-2+1
x-2x-2x=-2+1-7
-3x=-8 /:(-3)
x=2i 2/3